Representaciones de la liminalidad permanente en la película peruana “Paraíso” - Ramos Rojas, Ezzio Franco Paul (2021)
The film Paraíso (2010), by Héctor Gálvez, brings together various socio-historical processes experienced in Peru during the last quarter of a century. Through a semiotic analysis of the journey of the five protagonists, it is obtained that their narratives are unfinished or uncertain. To understand this incompleteness, the author updates the concept of liminality towards its permanent character. With this, a relationship is established with the context presented by the film: the post-conflict and the post-memory. It is also represented in other elements of the film, such as the perpetual transit of the characters, the absence of "final" stages in their stories, or the intrusion of "the real" into the frame. Permanent liminality allows a narrative and figurative analysis, no longer from or towards fixed and determined states, but within the margins, uncertainty and transition.